2019
DOI: 10.1096/fj.201802245r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and role of endoglin in cholesterol‐induced endothelial and vascular dysfunction in vivo and in vitro

Abstract: Our objective was to investigate the effect of cholesterol [hypercholesterolemia and 7‐ketocholesterol (7K)] on endoglin (Eng) expression and regulation with respect to endothelial or vascular dysfunction in vivo and in vitro. In vivo experiments were performed in 2‐mo‐old atherosclerosis‐prone apolipoprotein E–deficient/LDL receptor–deficient (ApoE−/−/LDLR−/−) female mice and their wild‐type C57BL/6J littermates. In in vitro experiments, human aortic endothelial cells (HAECs) were treated with 7K. ApoE−/−/LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…In fact, it has been reported that sEng contributes to endothelial dysfunction. Thus, sEng synergizes with hypercholesterolemia to aggravate endothelial and vessel wall dysfunction in vivo [43,45] and shows pro-inflammatory activity via nuclear factor-kappa B (NFkB) and interleukin 6 (IL6) in human endothelial cells in vitro [78]. Furthermore, exosomes from preeclamptic women induced vascular dysfunction by delivering sEng to endothelial cells [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been reported that sEng contributes to endothelial dysfunction. Thus, sEng synergizes with hypercholesterolemia to aggravate endothelial and vessel wall dysfunction in vivo [43,45] and shows pro-inflammatory activity via nuclear factor-kappa B (NFkB) and interleukin 6 (IL6) in human endothelial cells in vitro [78]. Furthermore, exosomes from preeclamptic women induced vascular dysfunction by delivering sEng to endothelial cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, preeclampsia can lead to serious, even fatal, complications for both mother and baby [41,42]. Noteworthy, several lines of evidence support a pathogenic role of sEng in cardiovascular conditions and diseases, including hypertension, endothelial dysfunction, anti-angiogenic activity, increased vascular permeability, vascular remodeling, and inflammation-associated leukocyte adhesion and transmigration [14,15,33,34,[42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of human umbilical vein endothelial cells (HUVEC) with 7KC results in increased expression of the cell adhesion molecules E-selectin, ICAM-1 and VCAM-1, and increased interactions between the endothelial cells and human monocytic THP-1 cells (Tani et al 2018 ). 7KC also increases the expression of endoglin, resulting in increased adhesion and transmigration of monocytes across human aortic endothelial cells (HAECs) (Vicen et al 2019 ). 7KC damages endothelial cells and increases the expression and release of clotting protein, von Willebrand factor (W. Li et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, endoglin modulates ALK-1 ligand binding and signalling. Hypercholesterolemia alters endoglin expression and signalling, causing endothelial or vascular dysfunction before the initiation of atherosclerotic lesions 45 . All these findings suggest the participation of the endothelial receptors ALK1 and endoglin in the regulation of atherosclerosis, mainly exerting an antiatherogenic effect.…”
Section: Discussionmentioning
confidence: 99%